Concerns About Improving the State System’s Performance in Emergency Scenarios - N., Quvandiqov A. (European Journal of Life Safety and Stability (2660-9630), 2023)
the issue of prevention and elimination of consequences of emergency situations is always relevant. In our country, a specially created system, the State System for Emergency Situations, deals with this issue. The improvement of this system is possible by planning the necessary measures assigned to it. When planning activities, it is necessary to separate the main activities from the rest. Such measures include the allocation of special events, increasing the readiness of government bodies, the correct distribution of forces and means, ensuring the stable operation of the media, etc.